ANALYSIS OF THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEMS ON THE EFFECTIVENESS OF DECISION MAKING IN E-COMMERCE COMPANIES - Ardiana Rahmadania; Devi Aulia Sari; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of management information systems (MIS) on the effectiveness of decision making in e-commerce companies. An effective MIS is able to provide accurate, complete, and real-time data to support managers in formulating strategies. A qualitative literature study was conducted by reviewing various relevant scientific sources. The results of the analysis show that MIS has a positive and significant influence on the effectiveness of decision making, with analytical technology, cloud computing, and big data playing an important role. Challenges such as data security, HR competency, and technology readiness still need to be addressed. Proper implementation of MIS can improve operational efficiency, customer satisfaction, and competitiveness of e-commerce companies.